THE IMPLEMENTATION OF INTEGRATED-APPROACH ON GERD (I-AGE) PROJECT IN FISHERMEN AS A MODEL OF INTERRELATION OF RESEARCH-BASED HEALTHCARE AND TEACHING - Ahmad Fariz Malvi Zamzam Zein (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
-